Global fisheries subsidies: An updated estimate. (July 2016) - Sumaila, U. Rashid; Lam, Vicky; Le Manach, Frédéric; Swartz, Wilf; Pauly, Daniel
Abstract: The aim of this paper is to provide an updated estimate of global fisheries subsidies. It builds on earlier estimates and methodologies to re-estimate and discuss the various types of subsidies provided by governments around the world. The results suggests that total subsidies were about USD 35 billion in 2009 dollars, which is close to the earlier estimate of 2003 subsidies once they are adjusted for inflation. Capacity-enhancing subsidies constituted the highest category at over USD 20 billion. For all regions, the amount of capacity-enhancing subsidies is higher than other categories, except for North America, which has higher beneficial subsidies. The analysis reveals that fuel subsidies constitute the greatest part of the total subsidy (22% of the total), followed by subsidies for management (20% of the total) and ports and harbors (10% of the total). Subsidies provided by developed countries are far greater (65% of the total) than those by developing countries (35% of the total) even though the latter lands well above 50% of total global catch. Asia is by far the greatest subsidizing region (43% of total), followed by Europe (25% of total) and North America (16% of total). Japan provides the highest amount of subsidies (19.7% of total), followed by the United States and China at 19.6% of total. Highlights: Global fisheries subsidies were estimated at about USD 35 billion in 2009 dollars. Harmful subsidies constituted the highest categories provided at over 20 billion. Harmful subsidies are highest category in all regions except North America. Fuel subsidies are largest of the total subsidy at 22%. Subsidies contributed by developed countries are 65% of the total.